Quasi-phase-matched high harmonic generation in gas-filled photonic crystal fibers - Anderson, PN; Wiegandt, F; Yu, F; Treacher, DJ; Lloyd, DT; Mosley, PJ; Hooker, SM; Walmsley, IA (Optical Society of America, 2017)
We investigate HHG in gas-filled PCFs with microjoule driving lasers. QPM is implemented for the first time, enhancing the flux at 30 eV by a factor of 60.